Chronic otitis media caused by Mycobacterium abscessus spp. massiliense treated with tigecycline in a 10-year-old child. (September 2018) - Myojin, Shota; Fukuoka, Kahoru; Kanemaru, Asako; Baba, Shintaro; Okamoto, Yuki; Suzuki, Hiromichi; Kamada, Keisuke; Yoshida, Atsushi; Kikuchi, Ken; Horikoshi, Yuho
Highlights: Mycobacterium abscessus is a rare but known causative pathogen of chronic otitis media in children. Tigecycline can be an acceptable option in the treatment of M. abscessus chronic otitis media. Emesis from tigecycline can be controlled well with the use of ondansetron. Abstract: Mycobacterium abscessus is one of the most pathogenic and chemotherapy-resistant rapidly growing mycobacteria. This Mycobacterium should always be considered as a possible cause of chronic otitis media in children, and treatment might be challenging because of its resistance to multiple antibiotics. There are no reports describing the therapeutic use of tigecycline for the treatment of chronic otitis media caused by M. abscessus . A 10-year-old boy was referred to Tokyo Metropolitan Children's Medical Center with a 7-year history of recurrent otitis media despite treatment with antibiotics and ventilation tubes. Cultures of the otorrhea yielded Mycobacterium abscessus spp. massiliense, and it showed multiple and high-level resistance. The boy required surgery and underwent initial treatment with clarithromycin, amikacin, and tigecycline for 4 weeks. He experienced emesis as a side-effect of tigecycline, which was well controlled with ondansetron. He was treated successfully with 3 months of subsequent oral clarithromycin and linezolid. This is the first pediatric case of chronic otitis media caused by M. abscessus treated with a tigecycline-containing regimen. Although the therapeutic use of tigecycline remains controversial, especially in the pediatric population, it can be an acceptable option in the treatment of chronic otitis media caused by M. abscessus .